Testing the CaR-FA-X Model: Investigating the Mechanisms Underlying Reduced Autobiographical Memory Specificity in Individuals With and Without a History of Depression - Sumner, Jennifer A. (2014)
Reduced autobiographical memory specificity (AMS) is an important cognitive phenomenon in major depressive disorder (MDD), but knowledge is lacking about its mechanisms. The CaR-FA-X model of Williams and colleagues proposed that three processes contribute to reduced AMS, alone or in interaction: capture and rumination (CaR), functional avoidance (FA), and impaired executive control (X). However, the entire CaR-FA-X model has not been tested. We addressed this gap in the literature by investigating contributions of the CaR-FA-X mechanisms to reduced AMS, alone or in interaction, in a subset of young adults (N=439) from the Northwestern-UCLA Youth Emotion Project. Participants were classified as those with (n=164) and without (n=275) a history of MDD at AMS assessment. They completed measures of: AMS; rumination (the brooding factor; CaR); childhood, adolescent, and early adulthood adversity (FA); avoidant coping (FA); and verbal fluency (X). Using structural equation modeling, we found greatest support for associations between reduced AMS and the capture and rumination, and impaired executive control mechanisms. In those with and without a history of MDD, brooding and verbal fluency interacted to contribute to reduced AMS. For participants without a history of MDD, lower verbal fluency (indicating impaired executive control) was associated with reduced AMS among those high on brooding. For participants with a history of MDD, lower verbal fluency was associated with reduced AMS among those low on brooding. The first finding was consistent with predictions from the CaR-FA-X model but the latter was not. Implications for conceptualizations of reduced AMS and its mechanisms are discussed.